The H3Africa policy framework: negotiating fairness in genomics. Issue 3 (March 2015) - de Vries, Jantina; Tindana, Paulina; Littler, Katherine; Ramsay, Michèle; Rotimi, Charles; Abayomi, Akin; Mulder, Nicola; Mayosi, Bongani M.
<x xml:space="preserve">Abstract</x> Human Heredity and Health in Africa (H3Africa) research seeks to promote fair collaboration between scientists in Africa and those from elsewhere. Here, we outline how concerns over inequality and exploitation led to a policy framework that places a firm focus on African leadership and capacity building as guiding principles for African genomics research.